Injuries among judokas during competition - Green, C. M.; Petrou, M. J.; Fogarty-Hover, M. L. S.; Rolf, C. G. (Scandinavian Journal of Medicine & Science in Sports, 2007)
Aims: To investigate the type and severity of injury sustained during judo competitions, and to investigate any possible correlation between injury rate and gender, grade, weight category and rapid weight loss.